2018
DOI: 10.3389/fphar.2018.00523
|View full text |Cite
|
Sign up to set email alerts
|

TRPC5-eNOS Axis Negatively Regulates ATP-Induced Cardiomyocyte Hypertrophy

Abstract: Cardiac hypertrophy, induced by neurohumoral factors, including angiotensin II and endothelin-1, is a major predisposing factor for heart failure. These ligands can induce hypertrophic growth of neonatal rat cardiomyocytes (NRCMs) mainly through Ca2+-dependent calcineurin/nuclear factor of activated T cell (NFAT) signaling pathways activated by diacylglycerol-activated transient receptor potential canonical 3 and 6 (TRPC3/6) heteromultimer channels. Although extracellular nucleotide, adenosine 5′-triphosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…The suppression of TRPC5 results in a reduction of ATP-induced NO production, thus promoting hypertrophic responses in cardiomyocytes. These results suggest that TRPC channels also function as negative regulators of cardiac remodeling [91].…”
Section: Cardiac Hypertrophymentioning
confidence: 86%
See 2 more Smart Citations
“…The suppression of TRPC5 results in a reduction of ATP-induced NO production, thus promoting hypertrophic responses in cardiomyocytes. These results suggest that TRPC channels also function as negative regulators of cardiac remodeling [91].…”
Section: Cardiac Hypertrophymentioning
confidence: 86%
“…Moreover, reported expression of TRPC5 in the heart and its change during heart failure vary among studies [88][89][90]. Recently we demonstrated that TRPC5 has an anti-hypertrophic effect in cardiomyocytes [91]. Based on the dogma mentioned above, the CaN/NFAT pathway is critical for cardiac hypertrophy.…”
Section: Cardiac Hypertrophymentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, TrPc channels have been regarded as drug therapeutic targets for cardiac hypertrophy (27). a number of previous studies have demonstrated that the expression of TrPc1, TrPc5, TrPc6 and TrPc7 are markedly upregulated in cardiac hypertrophy, and accumulating evidence has demonstrated that TrPc channels are related to cardiac hypertrophy (28)(29)(30)(31). Whether TrPc channels have a role in the development of cardiomyocyte hypertrophy, and whether TrPc channels are involved in the process of cardiomyocyte hypertrophy induced by ang ii remain unclear.…”
Section: Effect Of Skf-96365 On Cardiomyocyte Hypertrophy Induced By mentioning
confidence: 99%
“…Peer-reviewed version available at Cells 2020, 9, 173; doi:10.3390/cells9010173 from sinoatrial node, atrial or ventricular heart [14,[16][17][18][19]. In human cardiac tissues and/or neonatal rat cardiomyocytes mRNA of TRPC5 [20,21] and TRPC6 [22] were detected. In animal model, the expression of TRPC1/3-7 have been confirmed in adult rat and mouse ventricle and atrial cardiac myocytes either at mRNA or protein levels [13,23,24].…”
Section: Trpc Channels In the Cardiovascular Systemmentioning
confidence: 99%